Digital generation of the high quality audio signals with the NeXT computer - Roland-Mieszkowski, M.; Roland-Mieszkowski, D. (Canadian Acoustics, 1992)
A computer-based digital function generator can generate any arbitrary type of signal in the frequency range from 0 Hz to 20000 Hz, S/N=95 dB, and with no harmonic or intermodulation distortion (when based on 16-bit, 44.1 kHz-sampling rate D/A converter). Frequency stability is determined by a quartz clock in the D/A converter which has an accuracy in the order of 1/107. Generation of sinusoidal waves is of primary importance in digital synthesis since due to the Fourier theorem any periodic wave may be constructed via additive synthesis (an addition of pure tones with appropriate amplitudes and phases). There are many alternative methods to digitally generate pure tones. Very often real-time synthesis is accomplished by using a sine function look-up table. A limitation to this approach is the short length of the sine table. In order to synthesize any arbitrary frequency using the look-up table method, one has to synthesize the values of the sine function using an interpolation process. Interpolation between sine samples leads to the generation of harmonic and intermodulation distortion by this algorithm. Another problem is that synthesis of more complex signal (combinations of several sinusoids with certain amplitudes and phases) in real time could put too much performance demand on the computer's DSP chip or microprocessor